Factors that contribute to the success of AM/FM radio station managers - Banilao, Kenneth M.; Gonzales, Maila A.; Moro, Ritchel G.; Nograles, Mila L.
Executive summary - The write up of this research is summarized as follows : In Chapter One, present the problem that aimed to find out the factors that contribute to the success of AM/FM radio station managers. This chapter also presents the objectives of the study, which is to know how these variables contribute to their success and to know also the common factors that affect their success. Likewise, the theoretical and conceptual framework, definition of terms, hypothesis, scope and limitation and the significance of the study are also included in the chapter. The group identified four major variables, which is considered as factors for the success of fM?AM Radio Station Managers. These variables were illustrated in the diagram presented which includes motivation, working environment, station image and organizational commitment. In Chapter Two, Review of related literature and studies discusses some concepts and studies related to the present research. In Chapter Three, Methodology, introduces the research design and sampling design adapted in the conduct of the report, and procedures as well as the instruments adopted for data-analysis. In Chapter Four, Findings and Analysis, deals with the presentation, analysis and interpretation of data were gathered in connection with the specific objectives of this research. In Chapter Five, Summary, conclusion and Recommendation, states the major findings as well as the salient features of the study, the conclusions and recommendations derived from the results of the study.